Chemical novelty facilitates herbivore resistance and biological invasions in some introduced plant species - Sedio, Brian E.; Devaney, John L.; Pullen, Jamie; Parker, Geoffrey G.; Wright, S. Joseph; Parker, John D. (Ecology and evolution, 2020)
Ecological release from herbivory due to chemical novelty is commonly predicted to facilitate biological invasions by plants, but has not been tested on a community scale. We used metabolomics based on mass spectrometry molecular networks to assess the novelty of foliar secondary chemistry of 15 invasive plant species compared to 46 native species at a site in eastern North America. Locally, invasive species were more chemically distinctive than natives. Among the 15 invasive species, the more chemically distinct were less preferred by insect herbivores and less browsed by deer. Finally, an assessment of invasion frequency in 2,505 forest plots in the Atlantic coastal plain revealed that, regionally, invasive species that were less preferred by insect herbivores, less browsed by white‐tailed deer, and chemically distinct relative to the native plant community occurred more frequently in survey plots. Our results suggest that chemically mediated release from herbivores contributes to many successful invasions. Ecological release from herbivory due to chemical novelty is predicted to facilitate biological invasions by plants, but has not been tested on a community scale. We used metabolomics to assess the chemical novelty of invasive plant species at a site in eastern North America. Locally, invasive species were more chemically distinctive than natives. Among the invasive species, the more chemically distinct were less preferred by insect herbivores, less browsed by deer, and occurred more frequently in a large, regional network of forest plots. Our results suggest that chemically mediated release from herbivores contributes to many successful invasions.